Welfare implications of domestic land grabs among rural households in Delta State, Nigeria (2018)
Rural households are displaced from their lands without any plan in place to resettle or compensate them, for a promise of improvement in their living standards. This has not only resulted in a decline in the living standard of the rural populace, in terms of loss of land and livelihoods, the poor are also further marginalized and impoverished. This study examines the welfare implication of domestic land grabs among rural households in Delta State, Nigeria, employing primary data obtained from one hundred and seventy-three representative farming households. Descriptive analysis revealed that majority were low-income earners and engaged in farming as their major occupation. Econometric analysis revealed land size, secondary education, community leaders’ influence, compensation and the use to which the grabbed land was put into as some of the significant factors influencing domestic land grabs in the study area. Further, the size of land grabbed, no compensation for the use of land and low farm output were found to have negative effects on the welfare of the farmers. Thus, the need to intensify efforts to ensure that the rural populace is not being unreasonably dispossessed of its lands, becomes imperative. The need for commensurate compensation of rural households whose lands were grabbed and periodical checks on community leaders who positively influence domestic land acquisitions arbitrarily also becomes pertinent for improvement in the welfare of the farmers. This is especially so, if these small-scale farmers are to be significant drivers of global food security.